Menstrual Disruption with Exercise is not Linked to an Energy Availability Threshold - Lieberman, Jay L. (Med Sci Sports Exerc, 2018)
INTRODUCTION: Chronic reductions in energy availability (EA) suppress reproductive function. A particular calculation of EA quantifies the dietary energy remaining after exercise for all physiological functions. Reductions in LH pulse frequency have been demonstrated when EA using this calculation is < 30 kcal/ kg ffm·d(−1). PURPOSE: We determined whether menstrual disturbances (MD) are induced when EA is < 30 kcal/ kg ffm·d(−1). METHODS: Thirty-five sedentary, ovulatory women 18–24 yr (weight= 59.0 ± 0.8 kg, BMI= 21.8 ± 0.4 kg·m(2)) completed a diet and exercise intervention over three menstrual cycles. Participants were randomized to groups that varied in the magnitude of negative energy balance created by the combination of exercise and energy restriction. MD were determined using daily urinary estrone-1-glucuronide (E1G) and pregnanediol glucuronide (PdG), mid-cycle LH, and menstrual calendars. In a secondary analysis, we calculated EA from energy balance data and tested the association of EA with menstrual disturbances. RESULTS: A generalized linear mixed-effects model showed that the likelihood of a MD decreased by 9% for each unit increase in EA (odds ratio 0.91, 0.84 – 0.98, 95% CI, P=0.010). No specific value of EA emerged as a threshold below which MD were induced. When participants were partitioned into EA tertile groups (Low EA =23.4–34.1; n=11, Moderate EA =34.9–40.7; n=12, and High EA =41.2–50.1; n=12 (kcal/ kg ffm·d(−1))), E1G (p<0.001), PdG (p<0.001), and luteal phase length (p=0.031) decreased significantly, independent of tertile. CONCLUSION: These findings do not support that a threshold of EA exists below which MD are induced but do suggest that MD increase linearly as EA decreases. MD can likely be prevented by monitoring EA using a simplified assessment of metabolic status.